2010
DOI: 10.1523/jneurosci.0032-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Astn2, A Novel Member of the Astrotactin Gene Family, Regulates the Trafficking of ASTN1 during Glial-Guided Neuronal Migration

Abstract: Glial-guided neuronal migration is a key step in the development of laminar architecture of cortical regions of the mammalian brain. We previously reported that neuronal protein astrotactin (ASTN1) functions as a neuron-glial ligand during CNS glial-guided migration. Here, we identify a new Astn family member, Astn2, that is expressed at high levels in migrating, cerebellar granule neurons, along with Astn1, at developmental stages when glial-guided migration is ongoing. Biochemical and flow cytometry experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 47 publications
7
172
1
Order By: Relevance
“…Treatment with dynasore delayed the nuclear movement in the locomoting neurons (Fig. 6A,B), as previously reported (Wilson et al, 2010), and also decreased both the ratio of cells with a cytoplasmic dilation and the ratio of length to width of the nuclei ( Fig. 6C-E; supplementary material Movie 4).…”
Section: Inhibition Of Endocytic Trafficking Disturbs Dilation Formatsupporting
confidence: 87%
“…Treatment with dynasore delayed the nuclear movement in the locomoting neurons (Fig. 6A,B), as previously reported (Wilson et al, 2010), and also decreased both the ratio of cells with a cytoplasmic dilation and the ratio of length to width of the nuclei ( Fig. 6C-E; supplementary material Movie 4).…”
Section: Inhibition Of Endocytic Trafficking Disturbs Dilation Formatsupporting
confidence: 87%
“…[20][21][22][23] Alternatively, the cognitive impairment may be related to the fact that the deletion also includes part of the ASTN2 gene that codes for astrotactin 2, a brain protein possibly involved in neuronal migration. 11 A recent large study revealed that heterozygous copy number variations affecting the 3′-terminal part of ASTN2 or both ASTN2 and TRIM32 are significantly enriched in males with neurodevelopmental and neurobehavioral disorders. 13 In this study, the patient with cognitive impairment has a homozygous deletion of ASTN2, whereas the other patient, heterozygous for the ASTN2 deletion, does not present any intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50][51] Our analysis adds profilin1 as another novel regulator of CGN-glial cell interaction. In fact, we found reduced levels of vinculin and Mena in junctures of profilin1-deficient CGN and control glial cells.…”
Section: Profilin1 Is Important For Glial Cell Binding and Radial Migmentioning
confidence: 99%